Ontogenensis and developmental rate of the blow fly, Hypopygiopsis tumrasvini Kurahashi (Diptera: Calliphoridae) - S. Sanit (2018)
Blow flies of the genus Hypopygiopsis are considered forensically important. In Thailand, four Hypopygiopsis species coexist, i.e., Hypopygiopsis fumipennis, Hypopygiopsis infumata, Hypopygiopsis violacea and Hypopygiopsis tumrasvini. In this study, the ontogeny and developmental rate of H. tumrasvini eggs, larvae and pupae were determined in the laboratory chamber reared at 25.0 ± 2.0°C and 80.0 ± 5.0% RH. Larvae emerged from eggs 10-12 h after deposition. Mean length of the first, second, third (feeding phase), third (post-feeding phase) instars and puparia were 3.5 ± 1.1, 7.2 ± 1.1, 13.5 ± 1.8, 12.5 ± 0.5 and 9.0 ± 0.7 mm, respectively. The median development time for first, second, third instar (feeding phase), third instar (post-feeding phase) and pupariation period was 8 h, 10 h, 34 h, 22 d and 9-10 d, respectively. Developmental curve of the larval length indicated the rapid progression from 0 until 40 h from the first instar until the feeding third instar. Video recording of pupariation revealed the development of pupal respiratory horn beneath the larval integument at 27.0 h; whereas it protruded through the orifice of the integument at 27.5 h.